HAND HYGIENE CAMPAIGN AT LAFENE HEALTH CENTER - Heinrich, Ellen (My University, 2015)
The importance of proper hand hygiene in preventing disease is not a new concept in the field of medicine. Since the 1840’s when a physician, Ignaz Semmelweis, required his students clean their hands after performing autopsies, it has been recognized that cleaning hands can reduce mortality rates in hospitals.1 However, even though the importance of hand hygiene may be common knowledge, hand hygiene rates among medical professionals, including in both human and veterinary medicine, remain low.2, 3 This has led to increased efforts in researching the best ways to conduct hand hygiene campaigns among healthcare professionals to promote good hand hygiene among this group of people. The field experience described in this report took place at a human healthcare center, Lafene Health Center in Manhattan, Kansas. The field experience involved researching best practices for creating an effective hand hygiene campaign in a human healthcare setting and then executing a hand hygiene campaign at Lafene Health Center. A survey was distributed at the end of the campaign to gauge the perceived effectiveness
Keywords: Hand hygiene; Hand hygiene-campaign; Health promotion; Healthcare center; Hand sanitizer; Health communication; Public Health (0573)